Prospective study on the potential of RAAS blockade to halt renal disease in Alport syndrome patients with heterozygous mutations - Stock, Johanna; Tönshoff, Burkhard; Höcker, Britta (Pediatric nephrology, 2017)
BackgroundPatients with autosomal or X-linked Alport syndrome (AS) with heterozygous mutations in type IV collagen genes have a 1-20 % risk of progressing to end-stage renal disease during their lifetime. We evaluated the long-term renal outcome of patients at risk of progressive disease (chronic kidney disease stages 1-4) with/without nephroprotective therapy.MethodsThis was a prospective, non-interventional, observational study which included data from a 4-year follow-up of AS patients with heterozygous mutations whose datasets had been included in an analysis of the 2010 database of the European Alport Registry. Using Kaplan-Meier estimates and logrank tests, we prospectively analyzed the updated datasets of 52 of these patients and 13 new datasets (patients added to the Registry after 2011). The effects of therapy, extrarenal symptoms and inheritance pattern on renal outcome were analyzed.ResultsThe mean prospective follow-up was 46 ± 10 months, and the mean time on therapy was 8.4 ± 4.4 (median 7; range 2-18) years. The time from the appearance of the first symptom to diagnosis was 8.1 ± 14.2 (range 0-52) years. At the time of starting therapy, 5.4 % of patients had an estimated glomerular filtration rate of <60 ml/min, 67.6 % had proteinuria and 27.0 % had microalbuminuria. Therapeutic strategies included angiotensin-converting enzymer inhibitors (97.1 %), angiotensin receptor antagonists (1 patient), dual therapy (11.8 %) and statins (8.8 %). Among patients included in the prospective dataset, prevented the need for dialysis. Among new patients, no patient at risk for renal failure progressed to the next disease stage after 4 years follow-up; three patients even regressed to a lower stage during therapy.ConclusionsTreatment with blockers of the renin-angiotensin-aldosterone system prevents progressive renal failure in AS patients with heterozygous mutations in the genes causing AS. Considerable numbers of aging AS patients on dialysis may have heterozygous mutations in these genes (present in 1 % of total population) as underlying disease. Hence, greater alertness towards timely diagnosis and therapy has the potential to prevent progressive renal failure in most—if not all—AS patients with heterozygous mutations in the causal genes.
Published online: 11 July 2016
Gesehen am 28.08.2020